WORLD FINANCIAL CRISIS AND TENDENCIES OF FOREIGN ECONOMY DEVELOPMENT IN CHINA - Liu Tsepin (Наука и техника)
The paper is devoted to an analysis of world financial crisis in respect of foreign trade inChina. The main factors causing sharp decrease in the Chinese export and import are given in the paper. Measures undertaken by the government ofChinawith the purpose to overcome the crisis and also new tendencies taking place in the foreign trade are analyzed in details in the paper. The experience ofChinaconsisting in support of export and stimulation of internal requirements is rather useful for the Belarusian economists.